Psychomotor and Scientific Attitude Assessment to Simple Plane Materials through Application of Direct Instruction Learning Model - Azhar, Azhar (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
The purpose of this study was to analyze the psychomotor learning outcomes and scientific attitudes of students. This type of research is pre-experimental in the form of one shoot case study. The data analysis technique used is a descriptive analysis by assessing the psychomotor and scientific attitudes of students. The result of this research is that the students' psychomotor absorption ability is classified as good (80.67%). The effectiveness of learning is classified as effective (80.67%). Learning outcomes are classified as complete (88.8%) and classically, psychomotor learning objectives are declared incomplete (63.63%). The scientific attitude of students is classically categorized as high (74.27%). Analysis of psychomotor assessment and scientific attitude can help students achieve the target of completeness that has been set.